Factors that contribute to safety work culture in Dongwha Merbok, Kedah / Adilla Aini Mohammad Yasin @ Sape’ei and Siti Madihah Nordin - Mohammad Yasin @ Sape’ei, Adilla Aini; Nordin, Siti Madihah (2017)
We would like to thank God for the guidance and strength that has given to complete this study as required. Many thanks to our lecturer Dr Azlyn Ahmad Zawawi and our supervisor YM Tunku Nashril YM Tunku Abaidah for the guidance and wise counsel at critical points in addition to the commitment in spite of the awfully busy schedule. We would like to express our greatest appreciation and love to my family especially to our parent for their endless support and understanding in difficult situations whilst pursuing this course. To every person who contributed in this project paper that we could not mention their names, I am grateful for their cooperation. To my research respondents who answered my questionnaire and made by research complete we say thank you. Finally, we are intellectually indebted to the many academics whose research and writing provided valuable scholarly contribution to the successful completion of this piece of work.